The Meaning of moral do's form Javadi-Amoli's point of view - Mohammad hasan Amjadi; abdollah nasri (اخلاق وحیانی)
Explanation of philosophical theories of Professor Javadi Amoli in Semantic problems can be an introduction for rational defence of Realistic and eternal morality of Islam. In this view, we don’t use other moral or empiricism concepts for defining moral concepts. Thus, this theory categorize in the definism andgeneral naturalism, not in the specific naturalism. But this theory doesn’t define moral obligation concept based on divine commands and prohibitions like theological theories do, neither count as theological meta naturalism, it categorizes as philosophical meta naturalism theories, because it uses philosophical secondary intelligible or in other word necessity through other to define moral obligation. Also In terms of epistemology, in the theory of Professor Javadi Amoli concepts like moral obligation are conventional concepts and their statements includes Enshaei proposition not Ekhbari one, means they don’t give us any cognition about moral reality from abroad. So according to epistemology of moral obligation and statements including them, this theory is a noncognitive theory, but because conention of those concepts and Enshaei of those statements including them are based on the real benefits and corruptions, so they are not pure conventional and aren’t based on tastes and personal or plural emotions. Thus, this theory in terms of ontologically, is considered as reality moral obligations. However reality of this theory doesn’t mean that moral obligations have foreign instead, but it means that they are based on true and real beliefs which have been proven with logic in the theoretical philosophy.